Proceedings of the fourth international workshop on the identification of Dark Matter : (World Scientific, 2003)
The prestigious Identification of Dark Matter workshop series was initiated to assess the status of work that attempts to identify the constitution of dark matter. In particular, it aims to review the success of current methods that are used in the search for dark matter, as well as the new techniques that are likely to improve prospects for detecting possible dark matter candidates in the future. In the 5th International Workshop, special emphasis was placed on the recent results obtained in experiments searching for baryonic and non-baryonic dark matter. This volume comprises the high-quality review articles and papers contributed by leaders and promising young physicists who attended the conference. It provides the most recent updates on dark matter searches from both experimental and theoretical points of view.